BIOLOGIA DE ð˜šð˜ªð˜µð˜°ð˜µð˜³ð˜°ð˜¨ð˜¢ ð˜¤ð˜¦ð˜³ð˜¦ð˜¢ð˜ð˜¦ð˜ð˜ð˜¢ (OLIVER, 1819) (LEPIDOPTERA, GELECHIIDAE) EM CONDIÃ‡Ã•ES DE LABORATÃ“RIO - CÃ´nsoli, F. L.; Amaral Filho, B. F. (REVISTA DE AGRICULTURA, 2020)
BIOLOGIA DE ð˜šð˜ªð˜µð˜°ð˜µð˜³ð˜°ð˜¨ð˜¢ ð˜¤ð˜¦ð˜³ð˜¦ð˜¢ð˜ð˜¦ð˜ð˜ð˜¢ (OLIVER, 1819) (LEPIDOPTERA, GELECHIIDAE) EM CONDIÃ‡Ã•ES DE LABORATÃ“RIO